Understanding development conflict and violence: the cases of Bhutan, Nepal, North-East India and the chittagong hill tracts of Bangladesh - Rizal, Dhurba; Yokota, Yozo (New Delhi, 2006)
Understanding Development, Conflict and Violence: The Cases of Bhutan, Nepal, North-East India and the Chittagong Hill Tracts of Bangladesh "Understanding Development, Conflict and Violence: The Cases of Bhutan, Nepal, North-East India and Chittagong Hill Tracts of Bangladesh analyzes the relationship between development, conflict and violence, a most controversial, debated and studied theme in the social sciences. The study revolves around the core question: is development per se or the lack of it the cause of conflict and violence or have composite forces and factors played a role in its generation, accentuation or reduction? The book offers a mix of theoretical, empirical and statistical analysis, focusing on analyzing conflict and violence from composite perspectives. It vividly portrays, through robust and coherent empirical and statistical analysis, the myriad factors contributing to the theme under discussion. The book comprises an introduction and thirteen chapters besides the preface, bibliography, appendix and index. Simple, compact, coherent and critical, it lucidly challenges some of the fragmented views and segmental viewpoints of conflict and violence; critically examines the problem of intervention and absence of honest peace-brokers in the region and provides meticulous policy recommendations to drain the swamp of problems and map the trend of conflict in the area under consideration based on conflict framework analysis. It serves as an eye-opener to the layman, shallow academicians, donors and other professionals." Contents Preface. Introduction. I. A bird's eye view of South Asia. II. Methodological considerations. 1. From development to conflict and violence: conceptual framework. 2. Engineering evolution through conflict and violence: the case of Lhotsampa Bhutanese and refuges crisis. 3. Engineering evolution through conflict and violence: the case of Jumma people of Chittagong Hill Tracts of Bangladesh. 4. Engineering evolution.
Keywords: Violence